Collaborative Learning for ESL Classrooms : A Handbooks for Teachers - Sarala Thulasi Palpanadan; Venosha Ravana (Penerbit UTHM, 2022)
This book a teaching support tool for teachers and researchers looking to expand their knowledge on the effective conduct of collaborative learning for ESL (English as a second Language) teaching and learning. It includes comprehensive descriptions of facilitation, active interaction, feedback and reflection strategies with ready-to-use materials such as lesson plan checklist, feedback forms and reflective journal entries. Teachers can also learn about conflict resolution in a collaborative learning environment based on suggestion given. The sample of ESL activities designed based on the strategies discussed in the book may also help teachers to practice and customise more ESL lessons with collaborative learning activities based on their preferences. All the ideas discussed in this book are applicable foe ESL classroom learning and also e-learning.